Survival analysis of pregnancy associated breast cancer in Kelantan: a hospital-based retrospective cohort study - Abrar, Syed Sana (2023)
According to the World Health Organization, breast cancer was diagnosed in 2.3 million women in 2020, and approximately 6,85,000 deaths were recorded worldwide. The number of breast cancer patients in Malaysia is increasing at an alarming rate, with almost half of all breast cancer patients aged < 50 years. Breast cancer that develops during pregnancy or within 12-24 months of delivery is known as pregnancy-associated breast cancer (PABC). PABC patients may have poor clinical results and survival. Research exploring survival outcomes in pregnant breast cancer patients is limited, especially in Asian countries. The objective of this study was to compare the survival probability in PABC and non-PABC patients and identify if pregnancy is an independent prognostic factor in PABC. The study design was retrospective cohort. Two cohorts of breast cancer women, one pregnant cohort and another non-pregnant cohort, were followed for the survival outcome. Patients’ data from the Universiti Sains Malaysia (USM) and Hospital Raja Perempuan Zainab (HRPZ) II database from 1st January 2001 until 31st December 2020 was reviewed, and relevant information was extracted and recorded in a data collection form. The survival of the two groups of patients were analysed following the Kaplan-Meier method and compared using the Mantel-Cox log-rank method. Prognostic factors were analysed using Cox proportional hazard regression. A total of 35 patients in the PABC group were analysed and matched with 35 non-PABC patients in the 1:1 group and 70 non-PABC patients in the 1:2 group on the basis of age and year of diagnosis. The median (IQR) follow-up times were 30.93 (42.20), 25.17 (29.55), and 36.57 (58.25) months for the PABC, non-PABC (1:1), and non-PABC (1:2) groups, respectively. The median survival time in the PABC group was 40.32 months (95% confidence interval (CI), 0.00-94.18), 26.29 months in the 1:1 matched non-PABC group (95% CI 22.45-30.13; p=0.080) and 43.59 months in the 1:2 matched non-PABC group was (95% CI, 0.00-89.92; p=0.941). The 5-year survival of PABC, non-PABC (1:1), and non-PABC (1:2) was 47.54%, 25.69%, and 45.11%, respectively. There were no significant differences between groups; p=0.080 for 1:1 group and p=0.941 for 1:2 group. Pregnancy was not found to be an independent significant prognostic factor; adjusted hazard ratio (AHR) 0.56, 95% CI: 0.30, 1.03, p=0.063 for the 1:1 group and AHR 0.72, 95% CI (0.39, 1.28), p=0.266 for 1:2 group. The findings show that women diagnosed with PABC had non-significant difference of overall survival compared to non-PABC. Pregnancy is not an independent prognostic factor for the survival of breast cancer. This information may be useful when women with breast cancer are counselled and supports the option of beginning treatment with pregnancy continuation. However, due to the small sample size and low power of the study, the outcomes should be interpreted with caution.